ANALISIS KEPUASAN PELANGGAN JASA REPARASI SOUND SYSTEM DENGAN MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALISYS (IPA) PADA UD. MBS AUDIO PESANGGARAN BANYUWANGI - Gian Dwi Prasetyo; Endang Suprihatin; Muhammad Yusuf (Universitas Majalengka, 2024)
In facing intense competition in the repair service industry, UD. MBS Audio needs to engage in continuous efforts to enhance service quality and understand the changing dynamics of customer needs. Therefore, the aim of this research is to identify and improve service quality, as well as to design an action plan to enhance services at UD. MBS Audio. This research utilizes the Importance Performance Analysis (IPA) method as a tool to translate customer expectations related to product or service quality. From the calculation results using the IPA method, Quadrant IV is identified as the top priority because it is considered highly important by customers and requires special attention as its performance has not yet reached optimal satisfaction levels. Critical attributes in Quadrant IV include P1, P5, and P10. A thorough evaluation of service quality, divided into four quadrants based on the IPA method, indicates that attributes in Quadrant IV (Top Priority) need continuous improvement to enhance their performance. The company's main focus should be on sustained improvement efforts to enhance the performance of these attributes, such as the cleanliness and tidiness of the facilities provided by UD. MBS Audio, providing satisfactory service results according to customer preferences, and offering guaranteed warranties.